THE CONCEPT OF THE P/V GRAPH APPLIED TO CAPITAL INVESTMENT PLANNING. - Moore, Carl L. (The Accounting Review, 1962)
Abstract A graph similar in concept to the conventional profit-volume graph can be used in capital investment planning and can be especially useful in the analysis of relatively complex investment situations. The net discounted cash flow line for the most profitable investment candidate crosses the expected cost of capital line or zone at the highest point. In a large number of investment situations, this line will also cross the internal rate of return line at the highest discount rate and will be above all other discounted cash flow lines at all points. There are also investment situations in which the discounted cash flow lines for the various alternatives will cross. The line for the most profitable alternative does not necessarily lie to the right of the other lines when it crosses over the internal rate of return line. It will, however, be the highest line when it crosses the expected cost of capital line or zone. The line of limitation can be used to predict the cost within reasonable limits.